The Role of Private Capital Flows on Gross Domestic Product of Low, Middle and High Income Group Countries. - Choong, Chee Keong (2007)
There were many critics saying that private capital flows created financial volatility in the local financial market leading to volatile economic activity. Developing countries, therefore, face the challenge of designing economic policies and institutions to an increasingly integrated financial environment that secure the most benefits from capital inflows while reducing their vulnerability to sudden reversals. This dissertation addresses the role of different types of private capital, namely foreign direct investment (FDI), total foreign debt and portfolio investment in the global economy with particular reference to their effects on economic development in developing countries. The dissertation also aims to investigate to what extent the effectiveness of these private capital flows depends on the quality of financial system in the host countries. In addition, the path (or shock) of these capital flows in developing countries is also examined to provide meaningful policy implications. For example, if the private capital flows are characterized by a stationary (non-stationary, or contain a unit root), then it implies that shocks to private capital flows are temporary (permanent). To achieve these objectives, both panel unit root tests and generalised method of moments (GMM) panel data analysis are applied, covering 71 developed and developing countries over the period of 1988-2002. The empirical results indicate that: First, using three types of panel unit root tests, this study concludes that shocks to portfolio investment and foreign direct investment are temporary while total debt series is permanent in developing countries from year 1988 to 2002. Furthermore, the shock of East Asian financial crisis had significant impact in influencing the time path of these private capital flows. Second, while FDI and portfolio investment has positive and significant impact on economic growth in the countries under study depending on the stage of economic development, foreign debt have negative and significant impact in all countries under study. These findings are consistent and confirmed by using different types of financial development and stock market indicators. It seems that unfettered capital flows do not necessarily promote growth. In fact, some data suggest that foreign debt is deleterious to expansion under certain conditions. Third, the findings are in line with previous studies in the literature on private capital flows, quality of institutions and economic growth, which suggest that the consideration of institutional and financial absorptive capacity produces most of the significant results. The dissertation, therefore, suggests that for countries to benefit more from all types private capital flows, they have to achieve certain development level of domestic financial and banking sector, favouring the hypothesis that well-functioning domestic financial institutions in a recipient country is able to benefit more from private capital flows.